2021
DOI: 10.1155/2021/3656272
|View full text |Cite
|
Sign up to set email alerts
|

Network Pharmacology Analysis of the Therapeutic Mechanisms Underlying Beimu-Gualou Formula Activity against Bronchiectasis with In Silico Molecular Docking Validation

Abstract: Background. The classical Chinese herbal prescription Beimu-Gualou formula (BMGLF) has been diffusely applied to the treatment of respiratory diseases, including bronchiectasis. Although concerning bronchiectasis the effects and mechanisms of action of the BMGLF constituents have been partially elucidated, it remains to be determined how the formula in its entirety exerts therapeutic effects. Methods. In this study, the multitarget mechanisms of BMGLF against bronchiectasis were predicted with network pharmaco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 74 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Karşılanmayan amino asit artan varlığı, bronşektazinin başlamasına ve ilerlemesine katkıda bulunabilir, amino asit dengesi içinde farklı tedavi hedeflerinin belirlenmesi, bronşektazide hassas bir tıp yaklaşımına katkıda bulunur ve sonunda hastalığın ilerlemesini karakterize eden kısır girdapları kesintiye uğratır. amino asit üzerindeki klinik çalışmalar elde edilen veriler çok umut verici görünmektedir (27,28). Bununla birlikte, bronşektazide konak patojen etkileşimini daha iyi anlamak, farklı inflamatuar paternleri olan hastaları daha iyi karakterize etmek, diğer solunum yolu hastalıklarında kullanımda olan potansiyel tedavilerin rolünü anlamak ve bronşektazide yeni tedavi edilebilir özellikleri belirlemek için gelecekteki çalışmalara ihtiyaç vardır.…”
Section: Discussionunclassified
“…Karşılanmayan amino asit artan varlığı, bronşektazinin başlamasına ve ilerlemesine katkıda bulunabilir, amino asit dengesi içinde farklı tedavi hedeflerinin belirlenmesi, bronşektazide hassas bir tıp yaklaşımına katkıda bulunur ve sonunda hastalığın ilerlemesini karakterize eden kısır girdapları kesintiye uğratır. amino asit üzerindeki klinik çalışmalar elde edilen veriler çok umut verici görünmektedir (27,28). Bununla birlikte, bronşektazide konak patojen etkileşimini daha iyi anlamak, farklı inflamatuar paternleri olan hastaları daha iyi karakterize etmek, diğer solunum yolu hastalıklarında kullanımda olan potansiyel tedavilerin rolünü anlamak ve bronşektazide yeni tedavi edilebilir özellikleri belirlemek için gelecekteki çalışmalara ihtiyaç vardır.…”
Section: Discussionunclassified
“…Our previous study demonstrated the therapeutic mechanisms underlying Beimu-Gualou Formula for the treatment of bronchiectasis using network pharmacology methods. (Shen et al, 2021). Thereby, combination of network pharmacology, high throughput sequencing including transcriptomics, proteomics, metabolomics and intestinal flora sequencing, as well as experimental verifications can deeply elucidate the effects of R. cordifolia or R. cordifolia related prescriptions on gene and protein expression, metabolites and gut microbiota changes in bodies.…”
Section: Perspectives and Discussionmentioning
confidence: 99%
“…The approach involved target fishing, molecular interaction networking, and pathway enrichment analysis, which required the databases, such as TCMSP ( https://tcmsp-e.com/ ), BATMAN-TCM ( http://bionet.ncpsb.org.cn/batman-tcm/ ), PubChem ( https://pubchem.ncbi.nlm.nih.gov/ ), SwissTargetPrediction ( http://www.swisstargetprediction.ch/ ), DisGeNET ( http://www.disgenet.org/ ), CTD ( http://ctdbase.org/ ), GeneCards ( https://www.genecards.org/ ), STRING (version 11.0; https://string-db.org/ ), DAVID ( https://david.ncifcrf.gov/ ), and KEGG ( https://www.genome.jp/kegg/ ), as well as the software Cytoscape (version 3.7.1; https://cytoscape.org/ ). The analytical workflow was based on our previous report [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…The tool for semiflexible docking was AutoDock (version 4.2.6). The procedure was as reported previously [ 18 ].…”
Section: Methodsmentioning
confidence: 99%